Critical data storytelling in the composition classroom - Laflen, Angela, author; Utah State University Press, publisher (Colorado State University. Libraries, 2025)
Laflen offers a model for critical data literacy in multimodal composition that is adaptable for changing technological and educational circumstances. She provides multiple examples and activities to illustrate how to apply the model and provide needed skills for data literacy.--Provided by publisher.
1. Charting a Course for Data Storytelling in Multimodal Composition -- 2. Reading Data Stories Rhetorically -- 3. Cultivating Critical Data Communication Skills -- 4. Responding to and Assessing Students' Data Stories -- 5. Using Data as a Tool to Improve Teaching and Learning -- Conclusion: What Difference Does Data Storytelling Make?
Keywords: English language -- Rhetoric -- Computer-assisted instruction; English language -- Rhetoric -- Study and teaching (Higher) -- Data processing; Information visualization -- Study and teaching (Higher); Multimodal user interfaces (Computer systems); Artificial intelligence -- Educational applications